The non-toxigenic Clostridium difficile CD37 protects mice against infection with a BI/NAP1/027 type of C. difficile strain. (December 2015) - Zhang, Keshan; Zhao, Song; Wang, Yuankai; Zhu, Xuejun; Shen, Hong; Chen, Yugen; Sun, Xingmin
Abstract: Clostridium difficile CD37, a clinical isolate from the USA, does not produce toxin A, B or binary toxin. The aim of this study was to determine whether strain CD37 can protect mice against infection from a challenge with a toxigenic C. difficile strain. Three groups of mice (n = 10) were pretreated with a antibiotics cocktail for 5 days, switched to sterile water for 2 days, and given one dose of clindamycin (10 mg/kg) one day (day-1) before challenge (day 0) with a toxigenic C. difficile strain. Group 1 (CD37 + UK6) was given 10 7 C. difficile CD37 vegetative cells by gavage twice a day on days -1 and -2, followed by challenge with 10 6 spores of the toxigenic C. difficile UK6 (BI/NAPI/027) on day 0; Group 2 (UK6) was infected with 10 6 C. difficile UK6 spores on day 0; Group 3 (CD37) was challenged with 10 6 CD37 vegetative cells on day 0. Our data show that pre-inoculation of strain CD37 provided mice significant protection (survival, p < 0.001 between groups CD37 + UK6 and UK6) against subsequent infection with the strain UK6, while mice infected with CD37 only did not develop any symptoms of C. difficile infection (CDI). Our results highlight the potential use of CD37 as a therapeutic strain for the prevention of primary and recurrent CDI in humans. Highlights: The non-toxigenic Clostridium difficile CD37 is protective in mice against infection with a toxigenic strain. The non-toxigenic C. difficile CD37 has a potential to be used to prevent C. difficile infection in humans. The non-toxigenic C.difficile strains can be engineered to serve as mucosal/oral vaccines.